Predictive and Dynamic Signature for Antiangiogenics in Combination with a PD1 Inhibitor in Soft-Tissue Sarcoma: Correlative Studies Linked to the IMMUNOSARC Trial - Moura, David S; Lopez-Marti, Jesus M; Benesova, Iva; de Andrea, Carlos; di Lernia, Davide; Lacerenza, Serena; Mondaza-Hernandez, Jose L; Martin-Ruiz, Marta; Ramirez-Calvo, Marta; Grignani, Giovanni; Martinez-Trufero, Javier; Redondo, Andres; et al. (Clinical cancer research, 2024)
PURPOSE: The IMMUNOSARC trial combined an antiangiogenic agent (sunitinib) with a PD1 inhibitor (nivolumab) in advanced sarcomas. Here, we present the first correlative studies of the soft-tissue sarcoma cohort enrolled in this trial. EXPERIMENTAL DESIGN: Formalin-fixed paraffin-embedded and peripheral blood samples were collected at baseline and week 13. Formalin-fixed paraffin-embedded samples were used for transcriptomics and multiplex immunofluorescence, whereas peripheral blood samples were used for multiplexed immunoassays. Flow cytometry and Luminex assays were performed to validate translational findings in tumor-isolated cells and peripheral blood mononuclear cells derived from patients. RESULTS: The density of intratumoral CD8+ T cells, measured by multiplexed immunophenotyping, was significantly increased after treatment. This augment was accompanied by the dynamic significant increase in the gene expressions of CD86, CHI3L1, CXCL10, CXCL9, LAG3, and VCAM1 and the decrease in the expression levels of NR4A1. In peripheral blood, 12 proteins were significantly modulated by treatment at week 13. A score integrating the dynamic expression of the 7 genes and the 12 soluble factors separated 2 groups with distinct progression-free survival (PFS): 4.1 months [95% confidence interval, 3.5-not reached (NR)] versus 17 months (95% confidence interval, 12.0-NR), P = 0.014. This molecular score was predictive of PFS when applied to the normalized data determined in the baseline samples. CONCLUSIONS: Treatment with sunitinib and nivolumab inflamed the sarcoma microenvironment, increasing CD8+ T-cell density and the expression of several genes/proteins with relevance in the response to PD1 inhibitors. A molecular signature identified two groups of patients with distinct PFS for the combination of antiangiogenics plus PD1 inhibitor therapy.
Keywords: Aged; Antineoplastic Combined Chemotherapy Protocols; Angiogenesis Inhibitors; prognóza; protokoly protinádorové kombinované chemoterapie; lidé středního věku; senioři; lidé; ženské pohlaví; Nivolumab; Biomarkers, Tumor; Tumor Microenvironment; Sarcoma; Female; mužské pohlaví; tumor infiltrující lymfocyty; Adult; nádorové mikroprostředí; Middle Aged; inhibitory kontrolních bodů; nivolumab; inhibitory angiogeneze; Programmed Cell Death 1 Receptor; CD8-Positive T-Lymphocytes; Lymphocytes, Tumor-Infiltrating; Humans; Immune Checkpoint Inhibitors; dospělí; Male; CD8-pozitivní T-lymfocyty; Prognosis; nádorové biomarkery; antigeny CD279; sarkom